Mental territories : mapping the Inland Empire - Morrissey, Katherine G. (Cornell University Press, 1997)
Rarely recognized outside its boundaries today, the Pacific Northwest region known at the turn of the century as the Inland Empire included portions of the states of Washington and Idaho, as well as British Columbia. Katherine G. Morrissey traces the history of this self-proclaimed region from its origins through its heyday. In doing so, she challenges the characterization of regions as fixed places defined by their geography, economy, and demographics. Regions, she argues, are best understood as mental constructs, internally defined through conflicts and debates among different groups of people seeking to control a particular area's identity and direction. Applying the theoretical works of cultural studies to historical questions, Morrissey interprets the words and actions of railroad magnates, gravediggers, Indians on reservations, promoters, women homesteaders, union organizers, civil leaders, government agents, novelists, farmers, and investors. In the discourses about who belonged and who did not belong to defined communities or regions, residents participated in important representational struggles that had and continue to have significant material consequences.